2007
DOI: 10.1016/j.nuclphysb.2007.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic fluxes and moduli stabilization

Abstract: Stabilization of closed string moduli in toroidal orientifold compactifications of type IIB string theory are studied using constant internal magnetic fields on D-branes and 3-form fluxes that preserve N = 1 supersymmetry in four dimensions. Our analysis corrects and extends previous work by us, and indicates that charged scalar VEV's need to be turned on, in addition to the fluxes, in order to construct a consistent supersymmetric model. As an explicit example, we first show the stabilization of all Kähler cl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(80 citation statements)
references
References 21 publications
(49 reference statements)
1
79
0
Order By: Relevance
“…It has been suggested that magnetised branes along (1, 1)-cycles of the internal compactification space can be used to stabilise the Kähler moduli, as an alternative to non-pertubative effects, at a de Sitter vacuum through the induced D-terms [18,19,20]. The advantage of magnetic fluxes on D-branes, as opposed to non-perturbative effects and D3-contributions, is that these have an exact string description at weak coupling (i.e.…”
Section: D-terms In the Presence Of D7-branesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that magnetised branes along (1, 1)-cycles of the internal compactification space can be used to stabilise the Kähler moduli, as an alternative to non-pertubative effects, at a de Sitter vacuum through the induced D-terms [18,19,20]. The advantage of magnetic fluxes on D-branes, as opposed to non-perturbative effects and D3-contributions, is that these have an exact string description at weak coupling (i.e.…”
Section: D-terms In the Presence Of D7-branesmentioning
confidence: 99%
“…In most cases, dS vacua can only be obtained by 'uplifting' the vacuum energy in the presence of anti-D3 branes (D3-branes for short), which break though supersymmetry explicitly (KKLT scenario [4]). This situation can, in principle, be remedied if instead of D3-branes, D-term contributions are taken into account in the effective action [16,17,18,19,20,21,22], emerging from internal magnetic fluxes along the D7-branes world volume. String realisations improving the KKLT scenario are also possible within the so-called large volume scenario in Calabi-Yau compactifications [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…We hope we have convinced the audience, that twists and shifts produce (unoriented) models with few or no T's that can incorporate other mechanisms of moduli stabilization, e.g. open [37,[49][50][51][52] and closed string fluxes [21], (non) anomalous U (1)'s [53,54], instanton effects, ... . Explicit computations are feasible, though very systematic scans may be very time-consuming (thousands of characters, ...) [55].…”
Section: Discussionmentioning
confidence: 99%
“…First, we consider space-filling magnetized D9-branes, that is, D9-branes carrying constant magnetic fluxes on their world-volumes, wrapped on the orientifolded T 6 along with orientifold three-planes [8,12,14].…”
Section: Nine-branesmentioning
confidence: 99%
“…Such a scheme has been proposed with a real six-torus as the compactification manifold [14], albeit in conjunction with non-zero VEV of charged scalars. However, as mentioned above, the different kinds of RR charges of the configuration must add up to zero, for cancelation of tadpoles of all kinds.…”
Section: Seven-branesmentioning
confidence: 99%